2017
DOI: 10.1101/157941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taking off the training wheels: Measuring auditory P3 during outdoor cycling using an active wet EEG system

Abstract: Mobile EEG allows the investigation of brain activity in increasingly complex environments. In this study, EEG equipment was adapted for use and transportation in a backpack while cycling.Participants performed an auditory oddball task while cycling outside and sitting in an isolated chamber inside the lab. Cycling increased EEG noise and marginally diminished alpha amplitude. However, this increased noise did not influence the ability to measure reliable event related potentials (ERP). The P3 was similar in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
52
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(84 citation statements)
references
References 58 publications
13
52
1
Order By: Relevance
“…A group of studies compared mobile systems during stationary versus non-stationary conditions using well-established paradigms, informing reliability across testing settings. Auditory oddball tasks ( Debener et al, 2012 ; Scanlon et al, 2017 ; Zink et al, 2016 ) to elicit the P3 ERP can be performed in non-lab conditions. Even if significant artefacts may be present in a moving condition (i.e., biking freely in a university campus), above chance P3 single-trial classification is still possible ( Zink et al, 2016 ; see Fig.…”
Section: Current Challengesmentioning
confidence: 99%
“…A group of studies compared mobile systems during stationary versus non-stationary conditions using well-established paradigms, informing reliability across testing settings. Auditory oddball tasks ( Debener et al, 2012 ; Scanlon et al, 2017 ; Zink et al, 2016 ) to elicit the P3 ERP can be performed in non-lab conditions. Even if significant artefacts may be present in a moving condition (i.e., biking freely in a university campus), above chance P3 single-trial classification is still possible ( Zink et al, 2016 ; see Fig.…”
Section: Current Challengesmentioning
confidence: 99%
“…Similar to Zink et al (), we found a significantly reduced P3 during the mobile task of cycling. However, we were surprised to find a significantly decreased P2 and increased N1 while participants had been cycling outside (Scanlon, Townsend, Cormier, Kuziek, & Mathewson, ). Altogether, these studies show that, in comparison to nonmobile, quiet laboratory conditions, the P3 in an oddball task tends to be reduced during mobile tasks such as walking or cycling outside but not during stationary cycling inside, indicating that changes in the P3 were related to changes in the task (e.g., stationary vs. mobile).…”
Section: Introductionmentioning
confidence: 96%
“…Some works study the auditive odd-ball task ERPs while sitting versus pedaling. 73,74 In an other study, 75 subjects carry out an inhibitory task while walking versus sitting. Other studies include the analysis of pianists EEG ERPs and power spectrum while performing a simple tune, 57 the prediction of braking intention from ERPs, 76 and the effect of rhythmic auditory stimulation on auditory motor synchronization on Parkinson's disease patients.…”
Section: T0-mentioning
confidence: 99%
“…However, our sample is greater than those of recently published works on mobile EEG. 73,74,76 The gender representation is quite imbalanced, hence it is not possible to carry out any gender-related contrast analysis. We have carried out the data capture sessions inside rooms without working electrical equipment, but we have not ensured total electromagnetic isolation, i.e.…”
Section: T0-mentioning
confidence: 99%